Comunicação, educação e gênero: uma perspectiva crítica para a análise de experiências territoriais - Sambucetti, María Emilia (2017)
Communication and education are aligned to the gender perspective to expand its epistemological challenge, its social fields of implication and its political scope of transformation. By borrowing the power of this emergent articulation and dilution of their disciplinary boundaries, as a key to re-reading the world, the article puts into dialogue and analyzes the senses about "the educational"" present in two workshop spaces, inscribed in dissimilar social and institutional contexts. Firstly, the Communication, Art and Gender Workshop at the 8th Female Penitentiary Unit of Los Hornos, city of La Plata